European Politics towards Muslim-Migrants - N. Krutova-Soliman; E. V. Grinevich (Vestnik MGIMO-Universiteta)
Book review: Annemarie Profanter, Elena Maestri (2021). Migration and Integration Challenges of Muslim Immigrants in Europe. Series Title: Politics of Citizenship and Migration. Palgrave Macmillan. 289 p. https://link.springer.com/book/10.1007/978-3-030-75626-0